2017
DOI: 10.1016/j.schres.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of metacognitive beliefs as implicated in the self-regulatory executive function model in clinical psychosis

Abstract: This meta-analysis investigated whether the five metacognitive beliefs implicated in the Self-Regulatory Executive Function (S-REF) model (Wells & Matthews, 1994;Wells & Matthews, 1996) are elevated in people with clinical psychosis compared to people with emotional disorder and non-psychiatric controls. The review followed guidance set-out in the PRISMA statement. Primary analyses compared summary effect sizes on each sub-scale of the Metacognitions Questionnaire (MCQ) for people with psychosis and non-psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 59 publications
3
36
0
Order By: Relevance
“…Symptom correlates of the CAS observed in stress and emotional disorder generalize to psychosis confirming the universality of these relationships. In their systematic review, Sellers et al (2017) identified 51 eligible studies among which findings confirmed specific positive relationships between central elements of the CAS and experiences of psychosis and psychological distress.…”
Section: The Cognitive Attentional Syndromementioning
confidence: 98%
“…Symptom correlates of the CAS observed in stress and emotional disorder generalize to psychosis confirming the universality of these relationships. In their systematic review, Sellers et al (2017) identified 51 eligible studies among which findings confirmed specific positive relationships between central elements of the CAS and experiences of psychosis and psychological distress.…”
Section: The Cognitive Attentional Syndromementioning
confidence: 98%
“…Dozens of studies now document impairments in metacognition in individuals with, or at risk for, schizophrenia using discrete (based primarily on self‐report questionnaires) or expansive (based primarily on clinical ratings of narratives) definitions. Further, indexes of metacognitive impairment show associations with a wide array of clinical features, including positive, negative and disorganized symptoms, social and nonsocial cognition, motivation, self‐agency, insight, and functional outcomes.…”
Section: Recent Developments and Future Directions For Research On Comentioning
confidence: 99%
“…From another perspective (Wells, 2000), dysfunctional metacognitive beliefs have also been reported in schizophrenia. These include negative appraisals about the benefit of becoming involved in cognitive activities and heightened anticipation of the uncontrollability, and danger of thoughts (Sellers et al, 2016) and have been associated with positive symptoms (Baker and Morrison, 1998;Morrison et al, 2011), especially hallucinations Hill et al, 2012;Austin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%